TRADITIONAL COMPILATION MAJOR TRANSLATION IN NATIONAL CULTUR - Ostonova Sanam Nematovna (Scholar Express Journal, 2021)
This article is focused on the description of the most characteristic discrepancies in the linguistic picture of the world among representatives of the English, German, Russian and some other linguocultural communities and ways of neutralizing cultural barriers by means of translation that can cause “disruptions” in the process of mediated bilingual communication. In this regard, the problems of conveying the content of a literary text with special attention to its "cultural" components are investigated. At the same time, the author proceeds from the opinion expressed more than once by experts that national and cultural differences are one of the fundamental difficulties in translation.
Keywords: Culture; ethno-cultural aspects; traditions; translation